Is Homeopathy related to Chemical Thermodynamics? - Mihael Drofenik (Acta Medico-Biotechnica, 2021)
In the present article, biochemical equilibrium is used as a starting point for the application of the Le Chatelier–Broun principle in order to clarify mechanisms of homeopathic treatment. The application of chemical thermodynamics to the main homeopathic principles elucidates the well–known “Law of Similars”. In addition, the theory of intensive dilution of homeopathic remedies is discussed.